Some Aspects of Returns to Scale in Business Administration - Beckmann, Martin J. (Quarterly Journal of Economics, 1960)
Journal Article Some Aspects of Returns to Scale in Business Administration Get access Martin J. Beckmann Martin J. Beckmann Brown University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 74, Issue 3, August 1960, Pages 464–471, https://doi.org/10.2307/1883061 Published: 01 August 1960